High Blood Pressure among Students in Public and Private Schools in Maceió, Brazil. - Haroldo S Ferreira; Glícia Maris A Lúcio; Monica L Assunção; Bárbara Coelho V Silva; Juliana S Oliveira; Telma Maria M T Florêncio; Amandio Aristides R Geraldes; Bernardo L Horta (PLoS ONE)
Unlabelled The prevalence of hypertension in childhood is increasing, and investigation of its distribution is important for planning timely interventions. This study assessed the prevalence of high blood pressure (HBP) and associated factors in students between 9 and 11 years of age enrolled in public and private schools in Maceió, Brazil. A cross-sectional study was performed in a probabilistic sample of students (10.3 ± 0.5 years). The students were selected from a systematic sampling of 80 schools (40 public and 40 private). To maintain similar proportions of students existing in public and private schools in Maceió, 21 and 14 students were randomly selected from each public and private school, respectively. The prevalence ratio (PR) was estimated using Poisson regression. A total of 1,338 students were evaluated (800 from public schools and 538 from private schools). No differences were observed between school types in terms of student age and gender (p > 0.05). The prevalence of obesity (19.9% vs. 9.0%; PR = 2.2; 95% CI = 1.67-2.92) and hypertension (21.2% vs. 11.4%; PR = 1.86; 95% CI = 1.45-2.40) were higher in private schools. The association between high blood pressure and type of school (public or private) remained statistically significant even after adjustment for obesity (PR = 1.53; 95% CI = 1.19-1.97). In conclusion (a) students from private schools have higher socioeconomic status, BMI, and HBP prevalence compared to those of public school; (b) among the evaluated students, the prevalence of obesity only partially explained the higher prevalence of high blood pressure among students from private schools. Other factors related to lifestyle of children from private schools may explain the higher prevalence of HBP. This results show the need to implement measures to promote healthy lifestyles in the school environment, since children with HBP are more likely to become hypertensive adults. Therefore, early detection and intervention in children with HBP is an important action for the prevention of hypertension in adulthood.